SIMULATIONS OF ARGON GASEOUS ELECTRONICS CONFERENCE INDUCTIVELY COUPLED PLASMA REACTOR USING COMSOL MULTIPHYSICS - Pham Thi Tuoi; Pham Xuan Hien; Nguyen Thi Van Anh; Nguyen Thi Thuy Duong; Nguyen Quang Van (Journal of Applied Science and Technology, 2019)
In this study, a model of reactor inductively coupled plasma using Argon (Ar) has been studied using Comsol Multiphysics’s built-in Plasma Module